2019
DOI: 10.1590/1413-7054201943004919
|View full text |Cite
|
Sign up to set email alerts
|

Use efficiency and responsivity to nitrogen of common bean cultivars

Abstract: Common beans are the main source of protein in underdeveloped countries, and nitrogen (N) is one of the nutrients the most limits the productivity of this crop. This study, under field conditions, aimed to: a) determinate through efficiency indices how N is used by 16 cultivars of common beans; and b) classify these cultivars regarding use efficiency and responsivity to N application. The experimental design was in randomized blocks in split-plot scheme, with four replicates. Main plots consisted of 16 cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 14 publications
4
29
0
9
Order By: Relevance
“…SY increased under high N top-dressing (17.51%), corroborating a previous study that reported N as the macroelement that most influences SY in common bean crop (Barros et al, 2018). Similar results were also observed for 16 Brazilian carioca common bean cultivars which observed an increase of approximately 21.71% in plants under high N condition (Leal et al, 2019).…”
Section: Interaction Between Factors and Influence Of Nitrogen Fertilsupporting
confidence: 90%
“…SY increased under high N top-dressing (17.51%), corroborating a previous study that reported N as the macroelement that most influences SY in common bean crop (Barros et al, 2018). Similar results were also observed for 16 Brazilian carioca common bean cultivars which observed an increase of approximately 21.71% in plants under high N condition (Leal et al, 2019).…”
Section: Interaction Between Factors and Influence Of Nitrogen Fertilsupporting
confidence: 90%
“…The use of efficiency indices enables a better understanding of how the nutrient is utilized and for which organs it is destined in plants (Leal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…especially for physiological and utilization efficiencies, indicates that the spatial arrangement used, with the super-early hybrid of erect leaf architecture, did not favor the increase in leaf area, making it difficult for plants in the doublerow system to convert their better N nutrition into compounds such as proteins and carbohydrates in leaves and grains. Physiological efficiency indicates the amount of shoot dry mass increased for each kg of N accumulated in the shoots, and the utilization efficiency represents the amount of shoot dry mass increased for each kg of N applied via fertilizers(Leal et al, 2019).In general, the N use efficiency decreased with the increase in the dose applied as topdressing, as observed byFarinelli & Lemos (2010).Carvalho et al (2012) obtained a similar result when comparing 10 maize cultivars subjected to top-dressing fertilization with 40 and 160 kg ha -1 . The authors observed that there was no significant difference between the cultivars evaluated for the N content in the shoot dry mass.…”
mentioning
confidence: 99%
“…Além disso, estudos de Leal et al (2019) sobre eficiência e responsividade ao N por cultivares de feijoeiro comum classificaram a cultivar Pérola como eficiente no uso do N aplicado em cobertura. Outro ponto importante é que é comum a ausência de resposta significativa para o N foliar em estudos de adubação nitrogenada em feijoeiro comum, já que pode ocorrer efeito de diluição com o aumento de matéria seca proporcionado pela aplicação de N (PEREZ et.…”
Section: Discussionunclassified